The Role of Partnerships with Startups in Promoting Innovation and MSME Development for Poverty Alleviation - Nurcholidah, Lilik; Giansyah, Praditya; Tobroni, Syafaat Shobar; Lestari, Anasasi Apriliya Ayu; Lutfiana, Kharomah Siska (Technology and Society Perspectives (TACIT), 2024)
Partnerships with startups have become an effective strategy for promoting innovation and the development of Micro, Small, and Medium Enterprises (MSMEs), particularly in efforts to alleviate poverty. This study aims to delve deeper into the role of partnerships between SMEs and startups in fostering innovation and MSME development, as well as their impact on poverty alleviation. This research employs a literature review method with a qualitative approach. Data were sourced from the Google Scholar database for the period 2008 to 2024 using keywords related to the research topic. The study results indicate that partnerships between MSMEs and startups have significant potential in driving innovation, MSME development, and poverty alleviation. This collaboration enables technology transfer, enhancement of managerial capacities, and access to networks and resources that can improve MSME competitiveness. Concrete examples of successful partnerships, such as collaborations between fintech and MSMEs or e-commerce platforms with culinary MSMEs, illustrate how technology support and business strategies can expand markets and increase revenues.